BK polyomavirus: latency, reactivation, diseases and tumorigenesis - Zhou, Xianfeng; Zhu, Chunlong; Li, Hui (Frontiers in Cellular and Infection Microbiology, 2023)
The identification of the first human polyomavirus BK (BKV) has been over half century, epidemiological, virological, and phylogenetic data suggest that BKV co-evolved with their hosts, which accounts for high prevalence, latency, and symptomless reactivation. BKV has been mainly interlinked with BKV-associated nephropathy (BKVAN) in kidney-transplant recipients and hemorrhagic cystitis (HC) in allogeneic hematopoietic stem cell transplant recipients (HSCTRs). However, the mechanisms underlying BKV latency and reactivation are not fully understood and comprehensively discussed. As Merkel cell polyomavirus (MCV) was identified as a causative agent of malignant skin cancer Merkel cell carcinoma (MCC) since 2008, linking BKV to tumorigenesis of urologic tumors raised concerns in the scientific community. In this review, we mainly focus on advances of mechanisms of BKV latency and reactivation, and BKV-associated diseases or tumorigenesis with systematical review of formerly published papers following the PRISMA guidelines. The potential tumorigenesis of BKV in two major types of cancers, head and neck cancer and urologic cancer, was systematically updated and discussed in depth. Besides, BKV may also play an infectious role contributing to HIV-associated salivary gland disease (HIVSGD) presentation. As more evidence indicates that BKV plays a key role in tumorigenesis, it is important to pay more attention on its etiology and pathogenicity in vitro and in vivo.